FEATURES OF THE SELF-CONSCIOUSNESS FORMATION OF TEENAGERS WITH VIOLATIONS IN PRONUNCIATION OF SOUNDS - Didyk, Nataliia; Onufriieva, Liana (PSYCHOLOGICAL JOURNAL, 2018)
On the basis of many theoretical and experimental studies the article envisages the formation of teenagers’ self-consciousness to be based on the “Me-concept” of personality including a dynamic system of self-representations, covering cognitive, emotional and evaluative, and behavioral components. It is proved that consciousness is closely related to speech activities. The act of consciousness is the formation of perceptions of oneself that is not possible without speech. Self-consciousness is the result of the development of activities and intercourse. It is described that in the teenage age the leading activity is intimate-personal communication, therefore the awareness of oneself as a personality takes place among teenagers, first of all, in the process of teenagers’ intercourse with peers. During this period, teenagers are acutely experiencing disadvantages in the process of their speech, they easily notice non-standard or irregular forms of speech and violations in the pronunciation of sounds. It is established that there is a correlation between the nature of violations in the pronunciation of sounds and the peculiarities of self-consciousness among teenagers. This allowed us to find that the level of self-consciousness development of teenagers with violations in the pronunciation of sounds hardly differs from the age norm, but certain differences are still present. It is proved that the level of expressiveness of the difference depends on the nature of speech disorders and personality-based traits of a teenager. It is studied that children with fuzzy, but close to normal, pronunciation of sounds shouldn’t have significant effect on the formation of self-consciousness. It is experimentally found that teenagers with significant disorders in pronunciation of sounds are poorly understood by others, and this affects their position in the classroom, leads to bullying, lacks confidence, understated self-esteem, inferiority complexity, increased criticality to oneself, causing a difference between “Me-real” and “Me-ideal” and it leads to negative personality formations, as a result, they are more vulnerable and aggressive. The implementation of speech therapy correction and psychological support in the form of counseling, trainings, self-development programs, keeping diaries of self-examination, etc. are actual to overcome these negative personality-based new formations.